Pemikiran Sardar dan Azra dalam Pendidikan Islam, Transformasi Otoritas Digital, dan Moderasi Beragama (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the ideas of Ziauddin Sardar and Azyumardi Azra in three major areas: Islamic education, digital religious authority, and religious moderation. Using a library research approach, this article analyzes how Sardar’s Postnormal Times (PNT) framework explains global complexity, chaos, and contradictions that shape the future of Islamic thought and education. Meanwhile, Azra’s concept of Islam Nusantara and wasathiyah provides a historical and cultural foundation for constructing moderate Islamic identity in Indonesia. Findings indicate that Sardar emphasizes adaptive education oriented toward future literacy, while Azra highlights the integration of tradition, modernity, and local culture. In the context of digital authority, Sardar views the transformation as a structural effect of postnormal conditions driven by algorithmic systems, while Azra stresses the need to strengthen scholarly legitimacy based on sanad, institutions, and ethical guidance. Both perspectives converge on the importance of moderation. Sardar presents moderation as a strategy to manage global complexity, whereas Azra positions wasathiyah as the inherent identity of Islam in the archipelago. This study concludes that synthesizing both frameworks can strengthen Islamic education, stabilize digital religious authority, and reinforce Indonesia’s moderate Islamic identity in responding to contemporary challenges.